PENGARUH BRAND EQUITY TERHADAP LOYALITAS MAHASISWA TERHADAP LAPTOP DI UNIVERSITAS MUHAMMADIYAH PALEMBANG - Juariah, Juariah; Hamka, Hamka (Jurnal Ilmu Manajemen, 2016)
Brand equity is the added value given to products and services. This value can be reflected in how customers think. Feel and act to ward the brand, price, market share and profitablity owned company. Brand equity is an important intangible asset, which has psychological and financial value to the company. If the value of brand equity of a products or company is good for customers, it can because customers will loyal to the product. Accer, one of notebook brand has been already known by the customers especially female student. The objective of the study was to determine the influence of brand equity on customers loyalty on the brand of notebook among students of faculty of economic and business of university of muhammadiyah palembang. Data collection were done by using primary and secondary data, the techniques of collecting the data questionnaires and documentation. The technique of analyzis the data was using multiple linear regression analysis :According to equation Y = 2,379 + 0,542 X1 + 0,723 X2 + 0,325 X3 Fhitung > Ftabel Ho rejected which meant all dependent variables ( Brand equity ) consisted brand awarness, brand association and quality perception togetherly significantly influenced independent variabel ( customers loyality ). The T-test results from brand equity variable which influenced customers’ loyality were brand awareness T-test thitung29,305 > ttabel 2,013, brand associations T-test thitung 5,202 > ttabel 2,013, quality preceived T-test thitung 2,074 ttabel>2,013 it could be concluded that brand equity significally influenced on customers loyalty the brand of notebook among student of the faculty of economic and business of university of muhammadiyah palembang